Hippocampal temporal-parietal junction interaction in the production of psychotic symptoms: a framework for understanding the schizophrenic syndrome - Wible, Cynthia G. (Frontiers in Human Neuroscience, 2012)
A framework is described for understanding the schizophrenic syndrome at the brain systems level. It is hypothesized that over-activation of dynamic gesture and social perceptual processes in the temporal-parietal occipital junction (TPJ), posterior superior temporal sulcus (PSTS) and surrounding regions produce the syndrome (including positive and negative symptoms, their prevalence, prodromal signs and cognitive deficits). Hippocampal system hyper-activity and atrophy have been consistently found in schizophrenia. Hippocampal activity is highly related to activity in the TPJ and may be a source of over-excitation of the TPJ and surrounding regions. Strong evidence for this comes from in-vivo recordings in humans during psychotic episodes. The TPJ and PSTS play a key role in the perception (and production) of dynamic social, emotional and attentional gestures for the self and others (e.g., body/face/eye gestures, audiovisual speech, prosody). The single cell representation of dynamic gestures is multimodal (auditory, visual, tactile), matching the predominant hallucinatory categories in schizophrenia. Inherent in the single cell perceptual signal of dynamic gesture representations is a computation of intention, agency, and anticipation or expectancy (for the self and others). The neurons are also tuned or biased to detect threat related emotions. Abnormal over-activation in this system could produce the conscious hallucination of a voice (audiovisual speech), person or a touch. Over-activation could interfere with attentional/emotional gesture perception and production (negative symptoms). It could produce the unconscious feeling of being watched, followed or of a social situation unfolding along with accompanying perception of intent and agency inherent in those representations (delusions). Cognitive disturbances in attention, predictive social processing, agency, working memory, and a bias toward the perception of threat would also be predicted.